Penerapan Pendekatan TaRL Dalam Meningkatkan Hasil Belajar pada Mata Pelajaran Pendidikan Pancasila Kelas V UPT SD Negeri 060843 Medan Barat - Zulmihani Harahap; Mimi Rosadi; Ayu Melati Ningsih; Emce Ida Hutabarat; Aisyah Butar Butar (Journal on Education, 2024)
This research is Classroom Action Research. The research was carried out at UPT SD Negeri 060843 West Medan, with a sample of 20 students consisting of 8 man and 12 women. Learning is carried out using the Teaching at The Right Level approach which focuses on the level of students' understanding. This research data is presented in the form of tables and graphs. The results of research in cycle I obtained data from 5 students (25%) with very proficient criteria, 5 students (25%) with proficient criteria, and 10 students (50%) with not yet proficient criteria. and in cycle II, data was obtained that 8 students (45%) had entered the very proficient criteria, 7 students (35%) had entered the proficient criteria, and 4 students (20%) were still at the not yet proficient criteria. Based on the results of research carried out on learning material on Pancasila Education, Diversity of National Cultures in the Indonesian Territory using the Right Level Teaching approach in class V elementary school, it can be declared successful.